Clinical characteristics and in-hospital outcome of medical staff infected with COVID-19 in Saudi Arabia: A retrospective single-center study - Abohamr, Samah I. (Saudi Med J, 2020)
OBJECTIVES: To analyze the clinical characteristics and in-hospital outcomes among coronavirus disease 2019 (COVID-19) positive medical staff compared with those of public. METHODS: A total of 108 COVID-19-positive medical staff patients were included in the study from March 23, 2020 to June 15, 2020. Patients were analyzed for demographic data, clinical presentations, and in-hospital outcomes and compared against 661 COVID-19-infected patients of non-medical personnel. RESULTS: Mean age of medical staff patients was 44.05±13.9 years, most of whom were women (63.9%). The infected medical staff members consisted of 63 nurses (58.3%), 37 physicians (34.3%), 5 technicians (4.6%), and 3 pharmacists (2.8%). Smoking (60.2%) was the most frequent, followed by diabetes mellitus (37%). Of 108 COVID-19 infected medical staff, 18 (16.6%) were isolated in the intensive care unit (ICU), of which 14 (77.8%) were male, 16 (88.9%) were smokers, and 16 (88.9%) presented with pneumonia. Fatality ratio among medical staff patients was 4.6%. Male gender with odds ratios (OR) of 7.771 and 95% confidence intervals (CI) of 0.837-72.195 and a history of chronic kidney disease of (OR=10.778, 95% CI: 1.503-77.287) were predictors of death among the medical staff group. CONCLUSION: The incidence of COVID-19 infection among medical staff is quite high, but the occurrence of extreme illness and death is significantly low compared with the general community. Training should be implemented for all hospital staff on infection prevention techniques. Reliable and quick access for testing medical personnel is essential to maintain health, safety, and availability of health care workers during this pandemic.